INTEGRASI KECERDASAN BUATAN DALAM PEMBELAJARAN PAI: PELUANG & TANTANGAN - Nina Arifa; Hamdan; Hidayat Ma’ruf; Ridhahani Fidzi (CV. Adiba Aisha Amira, 2025)
Abstract Artificial Intelligence (AI) is increasingly developing and being applied in various fields, including education. In the context of Islamic Religious Education (PAI), the integration of AI offers great opportunities to improve the quality of learning, but also presents challenges that need to be considered. This article discusses how AI can be integrated into PAI learning, the benefits it offers, and the obstacles that may be faced in its implementation. In addition, this article presents various academic references that support the analysis of the opportunities and challenges of implementing AI in PAI.